(untitled) - 1942-; Johnston, Tony; Forbes, Bart (New York, 1995)
The narrator describes the excitement of having the train pull into the town of Jacksonville, Texas, when he was a boy.
Keywords: Railroads; Trains; City and town life; Fiction; Texas